2014
DOI: 10.1371/journal.pone.0115029
|View full text |Cite
|
Sign up to set email alerts
|

Differential Co-Expression between α-Synuclein and IFN-γ Signaling Genes across Development and in Parkinson’s Disease

Abstract: Expression patterns of the alpha-synuclein gene (SNCA) were studied across anatomy, development, and disease to better characterize its role in the brain. In this postmortem study, negative spatial co-expression between SNCA and 73 interferon-γ (IFN-γ) signaling genes was observed across many brain regions. Recent animal studies have demonstrated that IFN-γ induces loss of dopamine neurons and nigrostriatal degeneration. This opposing pattern between SNCA and IFN-γ signaling genes increases with age (rho = −0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 49 publications
(59 reference statements)
0
29
0
Order By: Relevance
“…Module M47 was negatively co-expressed with SNCA. Notably, a significant loss of negative co-expression between SNCA and interferon-gamma genes in the substantia nigra has been demonstrated in PD patients as compared to controls 41 . This loss may result from a downregulation of genes within M47 in the substantia nigra of PD patients, similarly as was observed in blood transcriptomics of PD [38][39][40] .…”
Section: Discussionmentioning
confidence: 97%
“…Module M47 was negatively co-expressed with SNCA. Notably, a significant loss of negative co-expression between SNCA and interferon-gamma genes in the substantia nigra has been demonstrated in PD patients as compared to controls 41 . This loss may result from a downregulation of genes within M47 in the substantia nigra of PD patients, similarly as was observed in blood transcriptomics of PD [38][39][40] .…”
Section: Discussionmentioning
confidence: 97%
“…Module M47 was negatively co-expressed with SNCA. Notably, a significant loss of negative co-expression between SNCA and interferon-gamma genes in the substantia nigra has been demonstrated in PD patients as compared to controls 42 . This loss may result from a downregulation of genes within M47 in the substantia nigra of PD patients, similarly as was observed in PD blood transcriptomics 3941 .…”
Section: Discussionmentioning
confidence: 97%
“…However, increasing evidence indicate that dysregulation of IFN signaling plays a role in ageing and neurodegenerative disease processes 2,3,4 . With respect to PD, genetic and functional studies have identified a link between IFN-γ and disease 5,6,11,13,14,15 . There is also considerable evidence that PD genes can synergize with inflammatory triggers in determining disease risk 16,49,50 .…”
Section: Discussionmentioning
confidence: 99%
“…Supporting a possible role of IFN-γ in the disease process, increased levels of IFN-γ in the serum, as well as increased production of IFN-γ by peripheral CD4+ T cells, have been detected in PD patients compared to healthy controls 11,12 . Moreover, a significant co-expression of α -synuclein and IFN-γ has been found within the substantia nigra of PD patients 13 . Experimental models also support this connection, whereby IFN-γ has been linked to selective, progressive, DA neurodegeneration in rodents 11,14,15 .…”
Section: Introductionmentioning
confidence: 97%